The Evaluation of the Oncologic Patient for Drug-Induced Pneumonitis - Swanson, Terra C.; Kinder, Brent W.; Clark, Joshua M. (Seminars in Respiratory and Critical Care Medicine, 2025)
The National Cancer Institute (NCI) estimates that over 2 million Americans will be diagnosed with cancer in 2025. A significant proportion of these patients will receive chemotherapeutics, radiation, molecularly targeted therapies, or immunotherapies—many of which are associated with pulmonary toxicity. Drug-induced interstitial lung disease (D-ILD) is a growing and well-recognized complication of cancer-related therapies, carrying substantial morbidity and mortality. In addition to its direct health impact, D-ILD often necessitates modification or discontinuation of cancer treatment, further complicating oncologic care. As such, pulmonologists must be proficient in the evaluation and management of suspected D-ILD. In this review, we propose a structured approach to assessing patients with malignancy who present with diffuse parenchymal lung disease. We also summarize commonly implicated cancer therapies and their associated pulmonary toxicities.
Keywords: drug-induced pneumonitis; drug-induced interstitial lung disease; interstitial lung disease; cancer therapy-related complications